Impoliteness Triggers and Strategies in Students’ Complaints: A Socio-Pragmatic Analysis - Dacalanio, Mark Aaron A.; Cani, Shine M.; Osiba, Grachelle T.; Syting, Christian Jay O. (CV. Tripe Konsultan, 2024)
This socio-pragmatic study aimed to unearth the impolite triggers and strategies used in students' complaints extracted from 100 online student complaints. Using Culpeper's Impoliteness Theory (1996, 2011, 2016), the study identified various impoliteness triggers, namely conventionalized and non-conventionalized impoliteness triggers. The former includes pointed criticisms, condescension, insults, unpalatable questions, dismissals, message enforcers, threats, silencers, negative expressives, redundant patterning, and fighting words. On the other hand, the latter involves non-conventionalized impoliteness triggers, which involve form-driven and bald-on-record impoliteness, red herrings, convention-driven impoliteness, rhetorical questions, and inflammatory expressions. In terms of impoliteness strategies, the study found the use of bald-on-record impoliteness, positive impoliteness, negative impoliteness, and sarcasm or mock impoliteness, with withhold impoliteness not observed in the online context. Understanding the linguistic patterns of impolite complaints in online contexts can help formulate strategies to mitigate conflict and promote more constructive interaction among students. This study may provide valuable insights for improving digital discourse and social interaction protocols.